HIGHER EDUCATION STUDENTS' PERCEPTION TOWARDS THE IMPLEMENTATION OF SYNCHRONOUS AND ASYNCHRONOUS LEARNING MODES - Shopia, Khilda; Hamid, Syifa Fadhilah; Purnawati, Purnawati; Isnaniah, Isnaniah (FKIP, UNIVERSITAS ISLAM SYEKH-YUSUF TANGERANG, 2023)
The perception of higher education students towards synchronous and asynchronous learning modes plays a vital role in determining the success of these pedagogical approaches. Students' preferences and attitudes towards these modes can impact their engagement, motivation, and overall learning outcomes. Thus, this research aimed to analyze the students’ perception on the modes of English learning activities employed a descriptive quantitative and qualitative approach. Students of all majors became the respondents and filled online questionnaire via Google form. There were 464 respondents filled in the questionnaire. The result showed that students were fully aware of the implementation, characteristics, and consequences of these two learning modes. Furthermore, students can shift and adapt with ease to the modes employed. Then, it can be concluded that students have adapted to the modes of learning and face no difficulty in the employment of synchronous and asynchronous classes.